Estudio del clima laboral y la satisfacción de los trabajadores, en la Distribuidora Granda CIA LTDA, de la ciudad de Loja periodo 2022 - Silva Hernández, Patricio Fernando (2023)
The interest in the development of the following investigative work entitled "Study of the work environment and worker satisfaction, in the Distribuidora Granda CIA LTDA, in the city of Loja, period 2022" arose with the purpose of knowing the performance and satisfaction of human talent. present in commercial companies in general, for which it was established as a general objective entitled. Study of the work environment and the satisfaction of the workers, aimed at specifying the events that occur on a day-to-day basis with the collaborators, as well as how to know if they are comfortable or dissatisfied. For its development, a methodological process was applied, a qualitative and quantitative approach was used, the information was obtained through the application of a survey where 52 workers who work in the company Distribuidora Granda CIA LTDA participated, it was designed with option questions. multiple, through the Likert scale, as well as the application of statistical techniques. The due analysis of the results was carried out by means of the statistical tool SPSS. Among the most relevant results we have that the physical conditions of the workplace are comfortable with 57.7%, while the promotion of teamwork is always given with 34.6%, it was also determined that the workers are somewhat dissatisfied with respect to to their remuneration with 40.4%, recognition and appreciation in the workplace is almost always given with 38.5%, and finally training is given with some frequency in 30.8%, generating a feeling of discomfort in workers. As the main conclusion, it was determined that the company does not fully meet some of the needs of the workers, resulting in unsatisfied collaborators. Finally, it is recommended to implement measures that help improve job development and performance, trying to obtain more satisfied workers, and therefore more productive in obtaining goals and objectives set by the company.